Factors Affecting on Basic Knowledge in Mathematics and Lao Language for First-Year Primary School Teacher Trainees at Luangprabang Teacher Training College, Year 2017 - 2018 - SILIVANH , Sommay; VATHANAVONG, Thongtiane; PHEWKHAMPHOM , Sisaket; INTHAVICHIT, Padaphet; Yangxang,; DUANGCHAN , Boy; CHITTHAVONE, Chanthaluck (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
The pumposes of this research were to study the factors affecting on basic knowledge in Mathematics and Lao Language for First-Year Teacher Trainees at Luangprabang Teacher Training College, Year 2017 - 2018. The factors were divided into 3 dimensions, First of them was personal factors: learning personality and studying habits, Second of them was family factor: guardians’ learning attend and Third of them was school environmental factors: interpersonal relationship between students, interpersonal between students and their teacher and Teacher behavior toward students. The 27 Samples were the First-Year Teacher Trainees at Luangprabang Teacher Training College, Year 2017 - 2018. The instrument was questionaires of factors affecting on basic knowledge in Mathematics and Lao Language of the 1st year, Primary Section of Luangprabang Teacher Training College. The data was analyzed by the Pearson Product Moment Correlation Ceofficient and Stepwise Multiple Regression Analysis. The results were as follows: there were significantly positive correlation among the factors affecting on basic knowledge in Mathematics and Lao Language for First-Year Teacher Trainees at Luangprabang Teacher Training College and 1 factor: Teacher behavior toward students (X7) at 0,01. There were significantly 1 factor affecting the factors affecting on basic knowledge in Mathematics and Lao Language for First-Year Teacher Trainees at Luangprabang Teacher Training College was Teacher behavior toward students (X7) at 0,01 levle. The significantly predicted equation of the factors affecting on basic knowledge in Mathematics and Lao Language for First-Year Teacher Trainees at Luangprabang Teacher Training College at 0,01 level were as follow: Interms of raw scores were and Interms of standard scores were